Indoor EKF localization algorithm based on RFID carrier phase - Liangbo XIE; Xixi LIU; Yong WANG; Mu ZHOU; Zengshan TIAN (Tongxin xuebao)
In order to solve the problem of low localization accuracy caused by indoor environment interference in the existing UHF RFID localization methods, an indoor extended Kalman filter (EKF) localization algorithm based on frequency hopping assisted RFID carrier phase was proposed.The virtual large bandwidth obtained by frequency hopping was used for rough distance estimation to realize multipath suppression, and the reliable dual frequency point selection and parameter optimization were completed through the phase after multipath suppression.Finally, EKF algorithm was used to realize high-precision and fast localization.Experimental results show that the average localization error of the proposed algorithm is 9.35 cm, and the real-time performance of the localization solution is nearly 10 times higher than the traditional integer solution method based on Chinese remainder theorem (CRT).